A comparison of cardiovascular risk indices in patients with polycystic ovary syndrome with and without coexisting nonalcoholic fatty liver disease. (26th August 2013) - Dawson, Alison J.; Sathyapalan, Thozhukat; Smithson, Jacqueline A. J.; Vince, Rebecca V.; Coady, Anne‐Marie; Ajjan, Ramzi; Kilpatrick, Eric S.; Atkin, Stephen L.
Summary Background Women with polycystic ovary syndrome (PCOS) have an adverse cardiovascular risk profile and an increased prevalence of nonalcoholic fatty liver disease (NAFLD), which is also associated with an adverse cardiovascular risk profile. Objective To compare the cardiovascular risk profile of women with PCOS alone and women with PCOS and NAFLD. Design, Setting and Participants Twenty‐five oligoanovulatory women with PCOS were screened for NAFLD (including liver biopsy if appropriate) and had their cardiovascular risk factors measured which included the inflammatory marker C‐reactive protein (CRP), endothelial function {measured using endoPAT 2000 and serum markers [intracellular adhesion molecule‐1 (ICAM‐1), vascular cell adhesion molecule‐1 (VCAM‐1), E‐selectin and P‐selectin]}, clot structure and function [maximum absorbance (MA) and lysis potential (LT)]. Results Twelve patients had confirmed PCOS without evidence of NAFLD, and 13 patients had confirmed PCOS with evidence of NAFLD. The PCOS and NAFLD group were heavier (BMI 43·9 ± 2·2 kg/m2) compared with the PCOS alone group (BMI 37·6 ± 1·4 kg/m2P = 0·03). There was no difference in CRP (7·57 ± 0·95 vs 6·59 ± 1·87 mm P = 0·62) or endothelial function (RH‐PAT 1·96 ± 0·1 vs 1·74 ± 0·16 P = 0·25), ICAM‐1 (221 ± 48 vs 250 ± 60 ng/ml P = 0·19), VCAM‐1 (2124 ± 78 vs 2314 ± 91 ng/ml P = 0·13), E‐selectin (33·9 ± 3·3 vs 39·5 ± 15·5 ng/ml P = 0·31) and P‐selectin (101·0 ± 6·6 vs 95·9 ± 10·2 ng/ml P = 0·69). There was no difference in clot formation or lysis. Conclusion The patients with PCOS and NAFLD were heavier compared with patients with PCOS alone. Despite this, we were unable to demonstrate differences in inflammatory markers, endothelial function or clot structure and function, suggesting that severity of steatosis is not the most important determinant of cardiovascular risk in PCOS.